Microplastic Distribution and Influence Factor Analysis of Seawater and Surface Sediments in a Typical Bay With Diverse Functional Areas: A Case Study in Xincun Lagoon, China - Wei, Yifan; Ma, Wengang; Xu, Qiang; Sun, Chunyang; Wang, Xinyuan; Gao, Fei (Frontiers in Environmental Science, 2022)
Microplastics come directly or indirectly from human activities. The bay and coastal areas are constantly under pressure from human activities, including tourism, fishing, and aquaculture. Microplastic pollution is now recognized as a great threat to bay environments. In this study, we assessed microplastics in the Xincun Lagoon Bay, which had multiple human activities, to understand whether human activities could directly reflect the pollution level of microplastics. The results showed the dominant microplastics were small (100–500 μm, 45.2%) and transparent (57.0%), mainly consisting of fibers (95.7%), and cellophane (54.4%) was the dominant polymer. The color, type, and component indicated that wastes from aquaculture, laundry wastewater in the Tanka fishing raft area, and domestic wastes from tourism were the primary sources of microplastics in Xincun Bay. During the rainy season, microplastic abundances in surface water and surface sediment at the outer bay were found to be significantly higher (108.8 ± 37.1 item/L and 250.4 ± 92.0 item/kg, respectively) than those found at the inner bay (34.3 ± 12.9 item/L and 167.6 ± 71.7 item/kg, respectively), which presented a reverse trend in the dry season (p < 0.01). Although Xincun bay has a relatively closed environment and diverse human activities, concentrated rainfall and strong winds could cause microplastic abundance inside the bay during the rainy season to be lower than that outside the bay. Furthermore, the comparison of microplastic abundances in the areas with intensive human activities and non-human activity areas indicated that the intensity of human activities could not directly reflect the pollution of microplastics in the lagoon bay. It is also necessary to consider the geographical and seasonal characteristics in order to explain the pollution degree of microplastics in a bay.